KONSTRUK FILSAFAT DAN AGAMA DALAM BINGKAI PERADABAN ISLAM - Moh. Rofik Fitrotullah (El-QUDWAH, 2013)
KONSTRUK FILSAFAT DAN AGAMA DALAM BINGKAI PERADABAN ISLAM Oleh: Moh. Rofik Fitrotulloh Pusat Pengembangan Bahasa Arab (PPBA) UIN Maliki Malang. Tlp. 085334441200. e-mail: alessandrorofik@yahoo.com Abstract Is the most perfect human beings and privileged among Allah is creation because awarded human reasoning. This feature is very fundamental and vital that distinguishes it from other creatures . With the feature of human thinking , deciding what is good and bad , and has the character of a very high curiosity. Tradition of thinking that has led to the tradition of philosophy, namely to think deeply about all that is. From this philosophical traditions emerged various disciplines of science, thus giving birth to the science and technology in containers based on sensory experience. In other words, the birth of the science and philosophy of science because of tradition, which is able to meet the intellectual void. While religion is supreme and ultimate truth that comes from God through revelation to the Prophet Muhammad SAW. Surely guiding people to the real truth. Thus fulfilled the void of spirituality in religion. Harmonization of intellectual and spiritual greatness will give birth to civilization based on two sources of Islamic law are the al-Qur’ân and al-Hadîth are the ideals of Muslims in historicism long way in life. Keywords: Constructs, Philosophy, Religion and Civilization